EFFECTIVE MANAGEMENT OF ODONTOGENIC INFECTIONS THROUGH CONTROLLED FASHION BY POLYMERIC DEVICE CONTAINING MOXYFLOXACIN - P., Gorle A.; V., Mahale H.; S., Patil C. (International Journal of Current Pharmaceutical Research, 2017)
Objective: Present work demonstrates the use of film that releases the drug at a pre-programmed manner. Several methods have been explored for management of moxifloxacin in dealing of Odontogenic infections which are mainly caused by necrotic pulp or by bacterial invasion from the periodontal tissue. These are usually mixed bacterial infections, and they penetrate mostly into the soft and bony oromaxillofacial tissues to produce submucosal infiltrates and abscesses. Methods: The films were developed with the intention to minimize the dose of a drug, to deliver definite concentration and to preserve dosage at its site for a longer period by this means gets a better patient compliance. Moxifloxacin films were prepared by solvent casting technique using gellan gumÂ at different concentrations and PEG 400 as plasticizers. Compatibility study such as FT-IR and DSC also performed to check the interaction between drug and excipients used. The formulations were evaluated for their thickness, weight uniformity, folding endurance, content uniformity, surface pH, In vitro drug release. Optimized formulations were subjected to in vitro antibacterial activity and stability studies to assess the effectiveness of the formulations. Results: Formulations shown the good uniformity of drug content, there was no any kind of effect on moisture loss test. Weight and thickness of the films were found to be uniform. Plasticizer like PEG400 was found to influence their effect on drug release as well as characteristics of films. Conclusion: In vitro studies revealed that the formulations provide the best alternative to prolong drug release at the end of 10 h and formulations remained stable with intact at ambient conditions. Â 